Clinical and economic analysis of Gastrodin injection for dizziness or vertigo: a retrospective cohort study based on electronic health records in China - Yunfeng Lai; Ruoning Wang; Wei Li; He Zhu; Shuyang Fei; Honghao Shi; Nan Lu; Carolina Oi Lam Ung; Hao Hu; Sheng Han (BMC, 2022)
Abstract Background Dizziness and vertigo are common clinical symptoms. Gastrodin injection has shown clinical effects on dizziness or vertigo. However, little is known about the effectiveness and costs of combining Gastrodin injection with conventional treatment on dizziness or vertigo in daily practice. This study aimed to analyze the clinical and economic effects of Gastrodin injection for patients with dizziness or vertigo in comparison to Extract of Ginkgo Biloba Leaves injection in real-world practice. Methods Data was collected from the Hospital Information System of 131 hospitals across China from January to December 2018. Patients whose primary discharge diagnosis was dizziness or vertigo according to ICD-10 diagnostic coding were included and divided into two samples: sample of dizziness or vertigo; sample of dizziness or vertigo, with the complication of cerebral infarction. Comparative analysis of the medical cost per hospitalization, hospitalization duration, effective rates, and cure rates between the group of Gastrodin injection and the group of Extract of Ginkgo Biloba Leaves injection was conducted. Propensity Score Matching was used to control potential confounding factors. Results In the sample of dizziness or vertigo, although there was no significant differences on hospitalization duration (P = 0.080), the group of Gastrodin injection was significantly better than the group of Extract of Ginkgo Biloba Leaves injection (P < 0.001) in terms of treatment effect and the per capita hospitalization cost. In the sample of dizziness or vertigo, with the complication of cerebral infarction, there was no significant difference (P = 0.371) in terms of hospitalization duration, but the group of Gastrodin injection was significantly better than the group of Extract of Ginkgo Biloba Leaves injection (P = 0.009) in terms of treatment effect, and significant difference regarding the per capita hospitalization cost (P < 0.001). Conclusions Gastrodin injection showed advantages for inpatients with dizziness or vertigo compared with Extract of Ginkgo Biloba Leaves injection. Future studies using prospective pragmatic controlled trials can test and explore more about the effects of Gastrodin injections on dizziness or vertigo.